Left atrio-vertebral ratio: A new computed-tomography measurement to identify left atrial dilation. Issue 1 (January 2016) - Baque-Juston, Marie; Volondat, Manuelle; Fontas, Eric; Roger, Coralie; Brunner, Philippe; Padovani, Bernard; Chevallier, Patrick
Highlights: Left atrium dilation is a frequent condition often unrecognized on CT scan. Left atrium dimensions are proportional to a patient's build. LAVR is the first CT measurement directly scaling the left atrium to a body element available on the image. The LAVRs are significantly higher in patients with cardiogenic pulmonary oedema. A LAVR >2.1 suggests left atrial dilation. Abstract: Background: Left cardiac chambers dilation, interstitial lung changes and pleural effusions are the characteristics of cardiogenic pulmonary oedema on computed tomography (CT) of the chest but mensuration of the left atrial size is not routinely performed. Cardiac chambers normal dimensions are known to be proportional to the patient's build and anthropomorphic data but adjustment of chambers dimensions to available elements seen on the axial CT images has never been evaluated before. Objectives: Our objective was to use data easily available on axial images to directly scale the left atrium. We chose to divide the left atrial diameter by the thoracic vertebral diameter, using the latter as a body-mass indicator. As a preliminary study, we aimed to evaluate the range of values of this left atrio-vertebral ratio (LAVR) by comparing patients suffering from cardiogenic pulmonary oedema with patients free of cardiac disease. We hypothesized that if the difference of values in these two populations of patients was significant enough, this ratio would be relevant and could be used as a quick criterion in different clinical situations. Method: Two radiologists reviewed CT scans of 32 of patients free of cardiac disease and 40 patients in acute cardiac failure. The maximum diameter of the left atrium at the level of the right inferior pulmonary vein was divided by the vertebral transverse diameter to generate a left atrio-vertebral ratio. Receiver operating characteristic curves identified the threshold associated with pulmonary oedema. Measurements and main results: The mean LAVR was 1.85 ± 0.27 in asymptomatic patients and 2.48 ± 0.35 in patients with pulmonary oedema. A LAVR of 2.1 yielded 85% sensitivity and 88% specificity for the diagnosis of cardiogenic pulmonary oedema. Conclusions: LAVR is a simple new measure directly scaling the left atrial diameter to the anthropomorphic characteristics of the patient. In our series, a ratio above 2.1 is strongly associated with cardiogenic pulmonary oedema indirectly suggesting left atrial dilation. The results were significantly different between the two populations of patients (no heart condition versus cardiogenic pulmonary oedema) suggesting a high potential for clinical application.